Effect of hyaluronic acid-stabilized silver nanoparticles on lettuce (Lactuca sativa L.) seed germination - Antunes, Débora R. [UNESP]; Forini, Mariana M.L.H. [UNESP]; Coqueiro, Yasmin A. [UNESP]; Pontes, Montcharles S.; Lima, Pedro H.C. [UNESP]; Cavalcante, Luiz A.F. [UNESP]; Sanches, Alex O. [UNESP]; Caires, Anderson R.L.; Santiago, Etenaldo F.; Grillo, Renato [UNESP] (Elsevier, 2024)
Nanotechnology has brought significant advancements to agriculture through the development of engineered nanomaterials (ENPs). Silver nanoparticles (AgNPs) capped with polysaccharides have been applied in agricultural diagnostics, crop pest management, and seed priming. Hyaluronic acid (HA), a natural polysaccharide with bactericidal properties, has been considered a growth regulator for plant tissues and an inducer of systemic resistance against plant diseases. Additionally, HA has been employed as a stabilizing agent for AgNPs. This study investigated the synthesis and effects of hyaluronic acid-stabilized silver nanoparticles (HA-AgNPs) as a seed priming agent on lettuce (Lactuca sativa L.) seed germination. HA-AgNPs were characterized using several techniques, exhibiting spherical morphology and good colloidal stability. Germination assays conducted with 0.1, 0.04, and 0.02 g/L of HA-AgNPs showed a concentration-dependent reduction in seed germination. Conversely, lower concentrations of HA-AgNPs significantly increased germination rates, survival, tolerance indices, and seed water absorption compared to silver ions (Ag+). SEM/EDS indicated more significant potential for HA-AgNPs internalization compared to Ag+. Therefore, these findings are innovative and open new avenues for understanding the impact of Ag+ and HA-AgNPs on seed germination.
Keywords: Hyaluronic acid; Nanomaterial; Seed germination; Seed-priming; Silver nanoparticle